Dedicated solar charging systems for electric vehicle (EV) batteries - Htay, Ei Lwin. (2015)
The world is relying on the fossil fuels for energy .These fuels are finite resources and gradually they would reach their ends. The importance of renewable energy plays a significant role today. Replacing the fuel dependent transportation with renewable and clean energy transportation would effectively save the fuels as well as the world from the climate changing, emission of greenhouse gases and other environment crisis. This project exploded the dedicated solar charging systems for electric vehicle (EV) batteries at houses. This report proposed two patterns of solar EV batteries charging systems. In System I, solar energy is stored in the storage battery bank during day time and the EV battery is charged at night. In System II, the owner needs to have two sets of EV battery for battery swap charging. One of the EV batteries is charged via charging system during the day time while the latter is consumed and vice versa. This report also studied the drawbacks of both charging systems and possible variable parameters to achieve the feasible charging system. The most feasible system was also recommended and concluded.